Current opinion on optimal systemic treatment for metastatic colorectal cancer: outcome of the ACTG/AGITG expert meeting ECCO 2013. Issue 12 (December 2014) - Price, Timothy J; Segelov, Eva; Burge, Matthew; Haller, Daniel G; Tebbutt, Niall C; Karapetis, Christos S; Punt, Cornelis JA; Pavlakis, Nick; Arnold, Dirk; Gibbs, Peter; Shapiro, Jeremy D
<x xml:space="preserve">Abstract</x> The treatment of metastatic colorectal cancer has evolved greatly in the last 15 years, involving combined chemotherapy protocols and, in more recent times, new biologic agents. Clinical benefit from the use of targeted therapy with bevacizumab, aflibercept, cetuximab, panitumumab and regorafenib in the treatment of metastatic colorectal cancer is now well established with median overall survival accepted as over 24 months, and with super selection for extended RAS patients higher again. The optimal timing of treatment options requires careful consideration of predictive biomarkers, and importantly the potential for interactions, to derive the maximal benefit. A group of colorectal subspecialty medical oncologists from Australia, the USA, the Netherlands and Germany met during ECCO 2013 to discuss current practice. Subsequent new data from the American Society of Clinical Oncology were also reviewed. This article reviews the evidence discussed in support of modern treatments for colorectal cancer and the decision-making behind the treatment choices, with their benefits and risks.